Problematika Mediasi Dalam Menyelesaikan Sengketa Pertanahan di Kantor Pertanahan Kabupaten Badung - Dewi, Dian; Nur Rahmanto; Dwi Wulan Titik Andari (Fakultas Hukum Universitas Mulawarman, 2025)
Mediation is a method for settling land disputes through negotiations mediated by a mediator. Its implementation, facilitated by the Land Office or the National Land Agency, is regulated in Article 43 paragraph 1 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning the Handling and Settlement of Land Cases. However, in practice, the Land Office of Badung Regency has consistently failed to This study examines the implementation of mediation over the past five years, from 2019 to 2024. It seeks to analyze the factors contributing to mediation failure and to identify strategies for strengthening the role of mediation in effectively resolving land disputes at the Land Office of Badung Regency. Employing empirical legal research, the study investigates how the law is applied in practice by exploring both internal and external factors that hinder successful mediation and proposing measures to improve its effectiveness. The findings indicate that mediation failures are caused by the absence of parties, lack of good faith, disagreements over proposed solutions, traditional beliefs conflicting with the law, and mediator-related internal factors. To enhance the effectiveness of mediation, strategic actions are needed, including raising public awareness of mediation benefits and procedures through consistent and intensive socialization, involving traditional and religious leaders, enhancing mediator competencies through thorough training, improving coordination among relevant institutions, and implementing regular monitoring and evaluation of the mediation process.